2008
DOI: 10.1108/14678040810906790
|View full text |Cite
|
Sign up to set email alerts
|

LibQUAL+TM in Iran: a subgroup analysis by gender

Abstract: Purpose -The purpose of this paper is to investigate the service quality of the central library of Iran University of Medical Sciences and Health Services (IUMS) from the viewpoints of female and male users of the library. Design/methodology/approach -The study was done using a LibQUAL+e survey, consisting of 22 core questions. The research sample included 361 users of the library and the results were interpreted on the basis of gap analysis. The mean values of gap scores for female and male users were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 8 publications
0
9
0
2
Order By: Relevance
“…In other words, library resources fail to meet members' minimum expectations. A parallel situation has been reported in studies of Hariri and Afnani (2008), Adam (2004), Derakhshan (2005), Ashrafirizi et al (2008), and Najafqolinejad (2007). It is essential for the national library to obtain access to approved national and international data bases in humanities, technical, engineering, 52 PMM 14,1 medical fields, and also develop updated resources of different disciplines based on national library's nature/function in the country.…”
Section: Expectations and Perceptionsmentioning
confidence: 70%
See 1 more Smart Citation
“…In other words, library resources fail to meet members' minimum expectations. A parallel situation has been reported in studies of Hariri and Afnani (2008), Adam (2004), Derakhshan (2005), Ashrafirizi et al (2008), and Najafqolinejad (2007). It is essential for the national library to obtain access to approved national and international data bases in humanities, technical, engineering, 52 PMM 14,1 medical fields, and also develop updated resources of different disciplines based on national library's nature/function in the country.…”
Section: Expectations and Perceptionsmentioning
confidence: 70%
“…There are several significant studies of service quality of academic libraries including Adam (2004), Derakhshan (2005), Godwin (2005), Kazempour (2006), Najafqolinejad (2007), Babaqeibi and Fatahi (2008), Hariri and Afnani (2008), Ashrafirizi et al (2008), QueensUniversity (2010), Asemi et al (2010), Killick (2010), Dowd (2010), Greenwood et al (2011), Mardani and Sharifmoghadam (2012), Pedramnia et al (2012), etc. Former studies applied LibQUAL+™ questionnaire across academic and research libraries but we believe this is the first time it has been used to assess a national library.…”
Section: Research Backgroundmentioning
confidence: 99%
“…A large body of literature investigated the use of LibQUAL+ instrument to measure the individual library performance (Jankowska et al , 2006; Johnson, 2007; Kayongo and Jones, 2008; Hariri and Afnani, 2008; Pedramnia et al , 2012). Apart from the academic libraries, studies conducted in other type of libraries and information settings revealed the appropriateness of the instrument (Thompson et al , 2007; Marshall, 2007; Ladhari and Morales, 2008; Morales et al , 2011; Voorbij, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Desde o momento em que foi criada, essa metodologia de avaliação de bibliotecas passou a ser utilizada em larga escala, principalmente em bibliotecas do meio universitário, sendo objeto de diversos estudos de caso dentro da literatura científica, tais como Herrera-Viedma, Lopes-Gijon, Avila-Fernandez (2008); Greenwood, Watson, Dennis (2011); e Hariri, Afnani (2008). Ressalta-se em tal literatura a capacidade de adaptação do LIBQUAL+® e sua objetividade nos parâmetros de avaliação, contrapondo-o a outras metodologias contemporâneas ao mesmo contexto teórico, tais como o Balanced Scorecard (Melo;Sampaio, 2010), o Question Point (Olszewski;Rumbagh, 2010) e o método do Cliente Oculto (Calvert, 2005).…”
Section: Marco Teóricounclassified